Solvent-free synthesis of enantioenriched β-silyl nitroalkanes under organocatalytic conditions - Dubey, Akhil K.; Chowdhury, Raghunath (Beilstein Journal of Organic Chemistry, 2021)
An enantioselective 1,4-conjugate addition of nitromethane to β-silyl α,β-unsaturated carbonyl compounds catalyzed by bifunctional squaramide catalysts has been developed. This methodology offers both enantiomers of β-silyl nitroalkanes in good to excellent yields (up to 92%) and enantioselectivities (up to 97.5% ee) under solvent-free conditions at room temperature. Control experiments reveal that the presence of a β-silyl group in the enones is crucial for high reactivity under the optimized reaction conditions.
Keywords: β-silyl α,β-unsaturated carbonyl compounds; β-silyl nitroalkanes; chiral organosilanes; organocatalysis; solvent-free synthesis

(untitled) - Fleming, I. (Sci. Synth., 2002)

(untitled) - Fleming, I.; Barbero, A.; Walter, D. (Chem. Rev., 1997)

(untitled) - Tamao, K.; Ishida, N.; Kumada, M. (J. Org. Chem., 1983)

(untitled) - Fleming, I.; Henning, R.; Plaut, H. (J. Chem. Soc., Chem. Commun., 1984)

(untitled) - Radner, F.; Wistrand, L.-G. (Tetrahedron Lett., 1995)

(untitled) - Yao, W.; Li, R.; Jiang, H.; Han, D. (J. Org. Chem., 2018)

(untitled) - Langkopf, E.; Schinzer, D. (Chem. Rev., 1995)

(untitled) - Denmark, S. E.; Liu, J. H.-C. (Angew. Chem., Int. Ed., 2010)

(untitled) - Fleming, I.; Lawrence, N. J. (Tetrahedron Lett., 1990)

(untitled) - Fleming, I.; Ghosh, S. K. (J. Chem. Soc., Chem. Commun., 1994)

(untitled) - Fleming, I.; Lee, D. (Tetrahedron Lett., 1996)

(untitled) - Lee, J.; Panek, J. S. (Org. Lett., 2011)

(untitled) - Wu, J.; Panek, J. S. (Angew. Chem., Int. Ed., 2010)

(untitled) - Pace, V.; Rae, J. P.; Procter, D. J. (Org. Lett., 2014)

(untitled) - Lee, K.-s.; Hoveyda, A. H. (J. Am. Chem. Soc., 2010)

(untitled) - Mita, T.; Sugawara, M.; Saito, K.; Sato, Y. (Org. Lett., 2014)

(untitled) - Rong, J.; Collados, J. F.; Ortiz, P.; Jumde, R. P.; Otten, E.; Harutyunyan, S. R. (Nat. Commun., 2016)

(untitled) - Sato, Y.; Takagi, C.; Shintani, R.; Nozaki, K. (Angew. Chem., Int. Ed., 2017)

(untitled) - Duong, H. Q.; Sieburth, S. M. (J. Org. Chem., 2018)

(untitled) - Su, B.; Lee, T.; Hartwig, J. F. (J. Am. Chem. Soc., 2018)

(untitled) - Huang, M.-Y.; Yang, J.-M.; Zhao, Y.-T.; Zhu, S.-F. (ACS Catal., 2019)

(untitled) - Zhu, J.; Chen, S.; He, C. (J. Am. Chem. Soc., 2021)

(untitled) - Zhang, L.; Oestreich, M. (ACS Catal., 2021)

(untitled) - Kranidiotis‐Hisatomi, N.; Yi, H.; Oestreich, M. (Angew. Chem., Int. Ed., 2021)

(untitled) - Hayama, T.; Tomoda, S.; Takeuchi, Y.; Nomura, Y. (Tetrahedron Lett., 1983)

(untitled) - Cunico, R. F. (J. Org. Chem., 1990)

(untitled) - Jiang, C.-R.; Zhao, C.-L.; Guo, H.-F.; He, W. (Chem. Commun., 2016)

(untitled) - Kitanosono, T.; Zhu, L.; Liu, C.; Xu, P.; Kobayashi, S. (J. Am. Chem. Soc., 2015)

(untitled) - Chowdhury, R.; Dubey, A. K.; Ghosh, S. K. (Eur. J. Org. Chem., 2020)

(untitled) - Shintani, R.; Okamoto, K.; Hayashi, T. (Org. Lett., 2005)

(untitled) - Balskus, E. P.; Jacobsen, E. N. (J. Am. Chem. Soc., 2006)

(untitled) - Kacprzynski, M. A.; Kazane, S. A.; May, T. L.; Hoveyda, A. H. (Org. Lett., 2007)

(untitled) - Zhao, K.; Loh, T.-P. (Chem. – Eur. J., 2014)

(untitled) - Zhang, Y.; Huang, J.; Guo, Y.; Li, L.; Fu, Z.; Huang, W. (Angew. Chem., Int. Ed., 2018)

(untitled) - Zhang, Y.; Huang, X.; Guo, J.; Wei, C.; Gong, M.; Fu, Z. (Org. Lett., 2020)

(untitled) - Zhang, Y.; Guo, J.; Han, J.; Zhou, X.; Cao, W.; Fu, Z. (Org. Biomol. Chem., 2021)

(untitled) - Chowdhury, R.; Dubey, A. K.; Ghosh, S. K. (J. Org. Chem., 2019)

(untitled) - Chowdhury, R.; Dubey, A. K.; Ghosh, S. K. (Asian J. Org. Chem., 2021)

(untitled) - Vakulya, B.; Varga, S.; Csámpai, A.; Soós, T. (Org. Lett., 2005)

(untitled) - Wang, J.; Li, H.; Zu, L.; Jiang, W.; Xie, H.; Duan, W.; Wang, W. (J. Am. Chem. Soc., 2006)

(untitled) - Yang, W.; Du, D.-M. (Org. Lett., 2010)

(untitled) - Zhang, G.; Zhu, C.; Liu, D.; Pan, J.; Zhang, J.; Hu, D.; Song, B. (Tetrahedron, 2017)

(untitled) - Cholewiak, A.; Adamczyk, K.; Kopyt, M.; Kasztelan, A.; Kwiatkowski, P. (Org. Biomol. Chem., 2018)